Accurate transcription of cloned Neurospora RNA polymerase II-dependent genes in vitro by homologous soluble extracts. - Tyler, B M (1985)
We have developed soluble extracts from Neurospora crassa capable of accurately initiating the transcription of cloned Neurospora protein-encoding genes by RNA polymerase II in vitro. The genes encoding glutamate dehydrogenase (am) and histones H3 and H4 were transcribed by the extracts, and transcription was sensitive to alpha-amanitin at 1 mg/ml. The 5' heterogeneity of the in vitro initiation reactions was highly specific. Of the 17 transcription initiation sites within the inducible qa gene cluster, only one minor site was used in vitro, suggesting that, in general, transcription from qa gene promoters requires at least one different protein from those required for transcription of the am and histone genes.